Problematika Konflik Norma Penerapan Jangka Waktu Hak Atas Tanah berdasarkan Peraturan Pemerintah Nomor 12 Tahun 2023 tentang Pemberian Perizinan Berusaha, Kemudahan Berusaha, dan Fasilitas Penanaman Modal Bagi Pelaku Usaha di Ibu Kota Nusantara - Aditya Khrisna Murti; Nawang Wulan; Andre Bagus Saputra (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
Rules are actually one of the objectives to achieve order and justice, however, sometimes there are overlapping rules that cause an imbalance in carrying out their functions. Law Number 5 of 1960 with Government Regulation Number 12 of 2023 is a form of overlapping regulations in relation to the term of land rights. The difference in the length of time for land rights as referred to in the two regulations creates a polemic in itself because of differences, including the time period for Cultivation Rights (HGU) with the proportion in Law No. 5/1960 given for a maximum period of 85 years, but in PP No. 12/2023 HGU rules change where the validity period of the HGU becomes 190 years. Therefore, this research will discuss related to the existence of a conflict of norms between the two rules and how the boundaries relate to the state's right to control and the setting of the time period for granting land rights in the capital city of the Archipelago. This study uses normative research with statutory and conceptual approaches. The results of this study are the need for harmonization of the two rules, especially for articles related to the term of land rights so that there is no conflict of norms in relation to state control rights in setting the time period for granting land rights.